(untitled) (Historia, 2021)
An essay in which an eminent American historian considers the significance of the terror attacks on the United States on 11 September 2001. The first Cold War crept in slowly and was not at all evident to most average Americans when President Truman addressed a joint session of Congress in March1947. No U.S. forces overseas, much less the United States itself, had been attacked, and Americans were obsessed with demobilizing from World War II and preventing a return of Great Depression conditions. So if Truman were to arouse the nation to resist world communism, he had to do what Senator Arthur Vandenberg recommended, which was to “scare the hell out of the American people”.